Gradient supercritical fluid chromatography coupled to mass spectrometry with a gradient flow of make-up solvent for enantioseparation of cathinones - Kolderová, Natalie; Jurásek, Bronislav; Kuchař, Martin; Lindner, Wolfgang; Kohout, Michal (Journal of chromatography. A, Including electrophoresis and other separation methods, 2020)
In the past two decades, supercritical fluid chromatography has evolved from a niche application to a comprehensive technology and a fully-fledged alternative to conventional high-performance liquid chromatography. In this study, we have focused on chiral separation of synthetic cathinones in gradient supercritical fluid chromatography coupled to mass spectrometry using an inverse gradient of a make-up solvent. Synthetic cathinones possess an amphetamine-like effect and, therefore, are frequently being offered on the Internet as a replacement for illicit drugs. Cathinones are chiral compounds, however, they are usually marketed and used as racemic mixtures. Since the effect of individual enantiomers can significantly vary, there is a need for the development of enantioseparation methods enabling to study the biological effects of individual enantiomers. Since cathinones are basic molecules, they are easily protonated (positively charged) under weakly acidic mobile phase conditions, which is a typical feature of supercritical mobile phases with an alcohol as an organic modifier. The positively charged species represent ideal analytes for ion exchangers, such as chiral zwitterion ion exchangers Chiralpak ZWIX (+) and Chiralpak ZWIX (-), which possess a positively and negatively charged unit in the molecular structure of the selectors. The presence of the positive charge in the selector's structure, functioning as a counter-ion for the positively charged analytes, significantly reduces the required amount of a buffer, which is plausible for hyphenation of such a separation system with mass spectrometry. For mass spectrometry hyphenated to supercritical fluid chromatography, the use of a make-up solvent is required to avoid analyte precipitation when using a low concentration of an organic co-solvent (modifier) in the super-/subcritical mobile phase. Hereby, we introduce a unique approach, which is based on the gradient introduction of the make-up to the post-column effluent. Using this approach, it is possible to keep constant the overall amount of the organic solvent (modifier and make-up) introduced into the mass spectrometer when using a gradient of the organic modifier. We show that the developed gradient elution method facilitates the chiral separation of all employed analytes, while the mobile-phase gradient compensation by the inverse make-up gradient enables their detection with high signal intensities.
Keywords: Chromatography, High Pressure Liquid; superkritická fluidní chromatografie; teplota; Stereoisomerism; stereoizomerie; Pressure; Alkaloids; tlak; Chromatography, Supercritical Fluid; alkaloidy; reologie; Solvents; Rheology; hmotnostní spektrometrie; Temperature; vysokoúčinná kapalinová chromatografie; rozpouštědla; Mass Spectrometry